2017
DOI: 10.1186/s13287-017-0675-2
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Isl1+ cardiac progenitor cells in small intestinal submucosa improves infarcted heart function

Abstract: BackgroundApplication of cardiac stem cells combined with biomaterial scaffold is a promising therapeutic strategy for heart repair after myocardial infarction. However, the optimal cell types and biomaterials remain elusive.MethodsIn this study, we seeded Isl1+ embryonic cardiac progenitor cells (CPCs) into decellularized porcine small intestinal submucosa extracellular matrix (SIS-ECM) to assess the therapeutic potential of Isl1+ CPCs and the biocompatibility of SIS-ECM with these cells.ResultsWe observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…A pilot study of cell-based therapies was introduced by Asahara et al, who observed that EPCs, isolated from human peripheral blood, contributed to vessel growth in ischemic tissues. This angiogenic potential has been replicated in clinical studies using cardiac progenitor cells [31,32] and ASCs [33]. However, excitement about EPCs and their phenotype, origin, and mechanism has been dampened because of unresolved questions, despite results demonstrating improved neovascularization in animal models of ischemia [34].…”
Section: Stem/progenitor Cell Therapymentioning
confidence: 99%
“…A pilot study of cell-based therapies was introduced by Asahara et al, who observed that EPCs, isolated from human peripheral blood, contributed to vessel growth in ischemic tissues. This angiogenic potential has been replicated in clinical studies using cardiac progenitor cells [31,32] and ASCs [33]. However, excitement about EPCs and their phenotype, origin, and mechanism has been dampened because of unresolved questions, despite results demonstrating improved neovascularization in animal models of ischemia [34].…”
Section: Stem/progenitor Cell Therapymentioning
confidence: 99%
“…For example, the SIS is made into a tubule with crosslinking of various biologically active factors and transplanted into animal to substitute carotid arteries [ 23 , 47 ]. SIS was loaded with cardiomyocytes and then was transplanted to the outer surface of infarcted myocardium in mice to repair heart function [ 16 ]. For meniscus reconstruction, meniscus cells and synovial-derived stem cells were also transplanted on SIS [ 19 ].…”
Section: Overview Of Sismentioning
confidence: 99%
“…Recent research documented that CSCs was involved in the heart failure (HF). 3,4 Thus, there need more investigations to investigate the mechanism of the function of CSCs in HF. The hypoxia was reported that involved in the HF.…”
mentioning
confidence: 99%